In Vitro Study of Mutagenesis Induced by Crocidolite-Exposed Alveolar Macrophages NR8383 in Cocultured Big Blue Rat2 Embryonic Fibroblasts - Yves Guichard; Laurent Gaté; Christian Darne; Marie-Claire Bottin; Cristina Langlais; Jean-Claude Micillino; Michèle Goutet; Schmit Julien; Binet Stéphane (Journal of Toxicology)
Asbestos-induced mutagenicity in the lung may involve reactive oxygen/nitrogen species (ROS/RNS) released by alveolar macrophages. With the aim of proposing an alternative in vitro mutagenesis test, a coculture system of rat alveolar macrophages (NR8383) and transgenic Big Blue Rat2 embryonic fibroblasts was developed and tested with a crocidolite sample. Crocidolite exposure induced no detectable increase in ROS production from NR8383, contrasting with the oxidative burst that occurred following a brief exposure (1 hour) to zymosan, a known macrophage activator. In separated cocultures, crocidolite and zymosan induced different changes in the gene expressions involved in cellular inflammation in NR8383 and Big Blue. In particular, both particles induced up-regulation of iNOS expression in Big Blue, suggesting the formation of potentially genotoxic nitrogen species. However, crocidolite exposure in separated or mixed cocultures induced no mutagenic effects whereas an increase in Big Blue mutants was detected after exposure to zymosan in mixed cocultures. NR8383 activation by crocidolite is probably insufficient to induce in vitro mutagenic events. The mutagenesis assay based on the coculture of NR8383 and Big Blue cannot be used as an alternative in vitro method to assess the mutagenic properties of asbestos fibres.